(untitled) (Al-Qamar, 2020)
Muslim Theologians wrestled with the thorny question: How to interpret Qur’anic descriptions of God that are couched in anthropomorphic imagery? Whereas certain factions insisted on assigning a literal meaning to such verses and thus affirming bodily characteristics for God (tashbih), rational theologians (mutakallimun) used metaphorical interpretation (ta’wil) as a principal strategy to resolve the contradiction between the outward meaning of the text and the dictates of reason. They argued that because reason is the sole means through which human intellect can ascertain the truth of revelation, its verdict must prevail when there arises a contradiction between reason and the apparent meaning of revelation. This paper elaborates on the approach that Ash’arite theologians took towards this question and records how the scope of metaphorical interpretation in the Ash’arite thought increasing widened over the generations.